The South African law of vicarious liability in delict and a comparison of the principles of other legal systems - Barlow, Trafford B.(Trafford Brereton),1906- (Stellenbosch : Stellenbosch University, 2012)
Thesis (LL. D.) -- University of Stellenbosch, 1937.